STRATEGY FOR DEVELOPING BLUE ECONOMIC POTENTIAL THROUGH SUSTAINABLE TOURISM IN THE COASTAL AREA OF SEMARANG CITY: STRATEGI PENGEMBANGAN POTENSI EKONOMI BIRU MELALUI PARIWISATA BERKELANJUTAN DI WILAYAH PESISIR KOTA SEMARANG - Pasaribu, Iwan Fadli; Hapsari, Trisnani Dwi; Prasetya, Ghozi Yoga (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Semarang City, the capital city of Central Java Province, holds significant potential for marine tourism developments due to its strategic location and various tourist destinations. However, this sector faces challenges in facilities, promotion, and management. This study was conducted from March to June 2024, and aims to analyze the potential for implementing a blue economy to support the development of marine tourism and contribute to formulating a blue economy-based strategy to support the development of sustainable marine tourism in Semarang City. The qualitative descriptive method with a case study approach applied data collection through interviews, observations, and literature reviews. Identification was carried out using a SWOT analysis to identify strengths, such as strategic location and diversity of destinations, as well as weaknesses in the form of limited facilities. Opportunities included the development of tourism packages and cultural events, while threats included environmental degradation and tidal flooding. Implementing a blue economy strategy can enhance marine tourism by improving promotional strategies, developing cultural and tourism events, and boosting conservation efforts, supported by improved management of facilities and infrastructure.